When Problems Only Get Bigger: The Impact of Adverse Childhood Experience on Adult Health - Novais, Márcia; Henriques, Teresa; Vidal-Alves, Maria João; Magalhães, Teresa (Frontiers in Psychology, 2021)
Introduction: Previous studies have shown that adverse childhood experiences negatively impact child development, with consequences throughout the lifespan. Some of these consequences include the exacerbation or onset of several pathologies and risk behaviors. Methods: A convenience sample of 398 individuals aged 20 years or older from the Porto metropolitan area, with quotas, was collected. The evaluation was conducted using an anonymous questionnaire that included sociodemographic questions, a list of current health conditions, questions about health risk behaviors, the AUDIT-C test (for alcohol consumption), the Fagerström test (for tobacco use and dependence), and the brief form of the Childhood Trauma Questionnaire, in Portuguese validated versions. Variables were quantified to measure adverse childhood experiences, pathologies, and risk behaviors in adult individuals for comparison purposes. Results: Individuals to have suffered different forms of adverse childhood experiences present higher rates of smoking dependence, self-harm behaviors, victimization of/aggression towards intimate partners, early onset of sexual life, sexually transmitted infections, multiple sexual partners, abortions, anxiety, depression, diabetes, arthritis, high cholesterol, hypertension, and stroke. Different associations between variables are analyzed and presented. Discussion and Conclusions: The results show that individuals reporting adverse childhood experiences have higher total scores for more risk behaviors and health conditions than individuals without traumatic backgrounds. Physical neglect appears as the ACE type that is most commonly found in individuals with the most prevalent health problems. Violence and suicidal behaviors have a strong positive association with all ACE factors. Moderate differences were found concerning age and sex. These results are relevant for health purposes and indicate the need for further research to promote preventive and protective measures.